PROSPECTS FOR THE DEVELOPMENT OF THE SCIENCE OF "FINANCIAL FORENSICS" IN THE FIGHT AGAINST FINANCIAL CRIMES (World Bulletin of Management and Law, 2023)
The current research aims to study the complementary relationship between financial culture in its dimensions (a culture of saving, a culture of spending, a culture of entrepreneurial ideas) and financial literacy in its dimensions (financial knowledge, financial behavior, financial attitudes), as the research was applied in a selected sample of insurance companies operating in the market Iraq Stock Exchange, and a set of statistical tools and programs were used to analyze and measure the correlation and influence relationships between the research indicators, which is a method)kurtosis&skewness(,)Amos.v.22(,)Spssv.22(The research reached a number of results, the most prominent of which was the existence of statistically significant correlation and influence relationships between financial literacy and financial literacy. The discovery of new ways of committing accounting crimes and the growth of various financial fraud schemes have created a need for the development of modern scientific fields. The article discusses the possibilities of the science "Financial Forensics" in the successful solution of the tasks of identifying, investigating and eliminating economic crimes. Statement of the problem: in recent years, the implementation of reforms of tax and budget legislation, pricing policy and the principles of a market economy in the financial and banking sector, the development of entrepreneurship, the emergence of new conditions in the management of the economy have led to modern changes in the economy. At the same time, they led to the expansion of various economic disputes, offenses in the economic sphere, as well as new types of fraudulent crimes, combined with legal actions in the financial sphere, which were rare or did not exist at all. In our opinion, such problems of our practice cannot be solved by the development of normative documents or the establishment of new standards and the introduction of specific procedures. An effective fight against this type of crime will also depend on the development of specific areas of science and the deepening of knowledge of personnel in this area. Aim of the research: development of modern science "Financial Criminology" in order to increase the effectiveness of the fight against economic crimes. Research methods: generalization of data, grouping, abstract-logical thinking, perspective forecasting, induction and deduction. Results and main conclusions: the successful activity of law enforcement agencies in the fight against economic and financial crimes depends on the availability of a complete picture of a specific forensic description of this type of crime. Therefore, the development of the "Financial Forensics" direction in this area is an effective solution in the disclosure and investigation of economic crimes, early detection of financial fraud schemes